Circulating Adipokines and Vascular Function: Cross-Sectional Associations in a Community-Based Cohort. Issue 2 (February 2016) - Zachariah, Justin P.; Hwang, Susan; Hamburg, Naomi M.; Benjamin, Emelia J.; Larson, Martin G.; Levy, Daniel; Vita, Joseph A.; Sullivan, Lisa M.; Mitchell, Gary F.; Vasan, Ramachandran S.
Abstract : Adipokines may be potential mediators of the association between excess adiposity and vascular dysfunction. We assessed the cross-sectional associations of circulating adipokines with vascular stiffness in a community-based cohort of younger adults. We related circulating concentrations of leptin and leptin receptor, adiponectin, retinol-binding protein 4, and fatty acid–binding protein 4 to vascular stiffness measured by arterial tonometry in 3505 Framingham Third Generation cohort participants free of cardiovascular disease (mean age 40 years, 53% women). Separate regression models estimated the relations of each adipokine to mean arterial pressure and aortic stiffness, as carotid femoral pulse wave velocity, adjusting for age, sex, smoking, heart rate, height, antihypertensive treatment, total and high-density lipoprotein cholesterol, diabetes mellitus, alcohol consumption, estimated glomerular filtration rate, glucose, and C-reactive protein. Models evaluating aortic stiffness also were adjusted for mean arterial pressure. Mean arterial pressure was positively associated with blood retinol-binding protein 4, fatty acid–binding protein 4, and leptin concentrations (all P <0.001) and inversely with adiponectin ( P =0.002). In fully adjusted models, mean arterial pressure was positively associated with retinol-binding protein 4 and leptin receptor levels ( P <0.002 both). In fully adjusted models, aortic stiffness was positively associated with fatty acid–binding protein 4 concentrations ( P =0.02), but inversely with leptin and leptin receptor levels ( P ⩽0.03 both). In our large community-based sample, circulating concentrations of select adipokines were associated with vascular stiffness measures, consistent with the hypothesis that adipokines may influence vascular function and may contribute to the relation between obesity and hypertension.